Engineered T Cells for the Adoptive Therapy of B-Cell Chronic Lymphocytic Leukaemia - Philipp Koehler; Patrick Schmidt; Andreas A. Hombach; Michael Hallek; Hinrich Abken (Advances in Hematology)
B-cell chronic lymphocytic leukaemia (B-CLL) remains an incurable disease due to the high risk of relapse, even after complete remission, raising the need to control and eliminate residual tumor cells in long term. Adoptive T cell therapy with genetically engineered specificity is thought to fulfil expectations, and clinical trials for the treatment of CLL are initiated. Cytolytic T cells from patients are redirected towards CLL cells by ex vivo engineering with a chimeric antigen receptor (CAR) which binds to CD19 on CLL cells through an antibody-derived domain and triggers T cell activation through CD3ζ upon tumor cell engagement. Redirected T cells thereby target CLL cells in an MHC-unrestricted fashion, secret proinflammatory cytokines, and eliminate CD19+ leukaemia cells with high efficiency. Cytolysis of autologous CLL cells by patient's engineered T cells is effective, however, accompanied by lasting elimination of healthy CD19+ B-cells. In this paper we discuss the potential of the strategy in the treatment of CLL, the currently ongoing trials, and the future challenges in the adoptive therapy with CAR-engineered T cells.